Mantra Penangkal Sakit di Desa Sei Kuning Kecamatan Rambah Samo Kabupaten Rokan Hulu - Ningsih, Ella Guspia; Ningsih, Asih Ria (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
Treatment with mantras is one form of traditional medicine that is still believed and practiced in Indonesia, including in Sei Kuning Village, Rambah Samo Subdistrict, Rokan Hulu Regency. This study aims to describe the form and meaning of mantras to ward off illness in the village. This research uses a qualitative method with an oral literature approach. Data were collected through in-depth interviews with informants who are mantra speakers in the village. The results showed that the form of mantras in Sei Kuning village is in the form of pantun. The types of antidote mantras found include mantras for getting stung, swollen body mantras, headaches, toothaches, and bone diseases. The results of this study show that the mantras in Sei Kuning village have various forms and are used to treat various diseases. The mantras also have deep meanings and contain cultural values that are important to preserve.